The Ganikhodjaev model of ABO blood groups - Saburov, Mansoor; Arshat, Mohd Saipuddin (IOP Publishing, 2017)
In 2010, N. Ganikhodjaev proposed the models of ABO and Rh blood groups of Malaysian people. Based on some numerical simulations, it was showed that the evolution of ABO blood groups of Malaysian people has a unique stable equilibrium. In this paper, we analytically prove that the Ganikhodjaev model of ABO blood groups has a unique fixed point.